MANAGING EDUCATIONAL EQUITY IN RURAL AND URBAN AREAS: A POLICY-BASED APPROACH - Ergasheva Ozodabonu Bahodirjon qizi, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article explores the issue of educational equity between rural and urban areas through a policy-based lens. Despite global efforts to promote equal access to quality education, significant disparities persist across geographic locations. The paper examines how educational policy, funding allocation, teacher deployment, infrastructure development, and digital inclusion impact equity in rural and urban contexts. Through policy analysis and international case comparisons, this study offers recommendations for equitable policy reforms aimed at bridging the urban-rural education divide.